Aspartic acid residues in BBE-like enzymes from Morus alba promote a function shift from oxidative cyclization to dehydrogenation - Nianxin Guo; Jun Gu; Qingyang Zhou; Fang Liu; Haoran Dong; Qi Ding; Qixuan Wang; Dongshan Wu; Jun Yang; Junping Fan; Lei Gao; Kendall N. Houk; et al. (Proceedings of the National Academy of Sciences, 2025)
Berberine bridge enzyme (BBE)-like enzymes catalyze various oxidative cyclization and dehydrogenation reactions in natural product biosynthesis, but the molecular mechanism underlying the selectivity remains unknown. Here, we elucidated the catalytic mechanism of BBE-like oxidases from Morus alba involved in the oxidative cyclization and dehydrogenation of moracin C. X-ray crystal structures of a functionally promiscuous flavin adenine dinucleotide (FAD)–bound oxidase, MaDS1, with and without an oxidative dehydrogenation product were determined at 2.03 Å and 2.21 Å resolution, respectively. Structure-guided mutagenesis and sequence analysis have identified a conserved aspartic acid that directs the reaction toward the oxidative dehydrogenation pathway. A combination of density functional theory (DFT) calculations and molecular dynamics (MD) simulations has revealed that aspartic acid acts as the catalytic base to deprotonate the carbon-cation intermediate to generate the dehydrogenated product, which otherwise undergoes a spontaneous 6π electrocyclization in the oxidative cyclization pathway to furnish the 2H-benzopyran product.